Elemental composition of palm-oil mill boiler flyash - Mohd. Yusoff, Mohd. Rashid (1987)
A total of 29 elemental concentrations were determined from two separate samples of palm oil flyash collected downstream of a palm oil mill boiler. These include Al, As, Ba, Br, Ca, Ce, Cl, Co, Cr, Cs, Dy, Eu, Fe, Ga, K, La, Lu, Mn, Na, Sb, Sc, Sm, Rb, Th, Ti, U, V, Yb and Zn. The results showed that potentially volatile elements like As, Ba, Br, Cl, Co, Cr, Cs, Sb, Rb, and Zn were enriched in the stack-ash emission as compared to retained-ash. Gallium, K and Na were intermediately enriched and Al, Ca, Ce, Eu, Fe, La, Lu, Mn, Sc, Sm, Th, Ti, V and Yb were equally concentrated in both samples.